Comparing Tsai-Wu and Tsai-Hill failure criteria for high-pressure vessel design under uncertainty - Novais, Henrique Cordeiro [UNESP]; Silva, Samuel da [UNESP]; Alves, Mariana Pimenta [UNESP]; Cimini Junior, Carlos Alberto [UNESP] (ABCM, 2023)
This study compares two widely used failure theories for characterizing composite materials: the Tsai-Wu and Tsai-Hill failure criteria. The paper’s main objective is to evaluate the performance of both criteria in a high-pressure vessel design project, taking into account uncertainties in material properties at the lamina level and in the internal pressure applied to the vessel. The analysis of histograms of failure index fluctuations reveals that, contrary to a purely deterministic approach, each failure criterion can be more or less conservative when there is variability in the system due to different factors. Additionally, a global sensitivity analysis using Sobol indices was conducted to determine the contributions of individual inputs to the output uncertainty. This probabilistic approach emphasizes the importance of considering uncertainty analysis to design structures that are both safer and more cost-effective.

Este estudo compara duas teorias de falha amplamente utilizadas para caracterizar materiais compostos: os critérios de falha de Tsai-Wu e Tsai-Hill. O principal objetivo do artigo é avaliar o desempenho de ambos os critérios em um projeto de design de vaso de alta pressão, levando em consideração incertezas nas propriedades dos materiais ao nível da lâmina e na pressão interna aplicada ao vaso. A análise dos histogramas das flutuações do índice de falha revela que, contrariamente a uma abordagem puramente determinística, cada critério de falha pode ser mais ou menos conservador quando há variabilidade no sistema devido a diferentes fatores. Além disso, uma análise de sensibilidade global usando índices de Sobol foi realizada para determinar as contribuições de entradas individuais para a incerteza de saída. Essa abordagem probabilística enfatiza a importância de considerar análises de incerteza para projetar estruturas que sejam tanto mais seguras quanto mais econômicas.
Comparação dos critérios de falha de Tsai-Wu e Tsai-Hill para o projeto de vasos de pressão de alta pressão sob Incerteza
Keywords: Composite materials; Failure criteria; High-pressure vessels; Uncertainty analysis; Sobol indices